SISTEM INFORMASI PENDAFTARAN MURID BARU PADAMTS RAOUDHOTUL MUHAAJIRIN BERBASIS WEB - Nurul Adinda Prasetianingsih (2023)
Student Admission is an activity that annually held by school to recruit someone to become their student, one of them is MTs Raoudhotul Muhaajirin. In the admission process, MTs Raoudhotul Muhaajirin still uses the conventional method, which is still using paper forms. This method can also cause data loss and also difficulties in compiling it into an archive. From the existing problems, we need an information system that can minimize the constraints that occur in conventional methods. In this new system, informations about admission, registration forms, checking selection results, and re-registration will be made in the form of a website. This website was created using HTML, CSS and PHP, as well as MySQL as the database server